Criteria for the regional allocation of public resources - Miranda, Casimiro V., Jr. (1988)
Based on a spatial development policy objective of continuous regional growth to reduce inter regional gap and unemployment, the paper develops simple criteria for the regional allocation of public resources for development from a regional growth model that uses the well-known Harrod-Domar growth equation as extended by neoclassical production function.
Keywords: Resource allocation; Public spending; Regional economic disparities